Neutral lipid profile of sago worm, the larva of weevil rynchophorus ferrugineus - Mohd. Ali, Ozair; Chu, K. L.; Wang, C. W. (2006)
The larva of the weevil Rynchophorus ferrugineus is popularly known as sago worm. The sago worms were purchased from the wet market in Kuching, Sarawak. The fat tissues were dissected separately from the viscera and the cuticle. The neutral lipid content of the fat tissue was extracted with 150 ml of dichloromethane by using a Soxhlet apparatus. The neutral lipid content per gm fat tissue (fresh weight) from the viscera was found to be 59.8% whereas that from the cuticle was 11.7%. The profile of triacylglycerols was analyzed by using high performance liquid chromatography (Waters 501 HPLC pump) equipped with evaporative light scattering detector (ELSD, VAREX MKIII). The HPLC column used was Supelcosil LC-18 column and the solvent system was acetonitrile /dichloromethane (68:32,v/v). The identification of triacylglycerols was carried out using purified olive and linseed oils and commercially available lipid standards. From the HPLC-ELSD chromatograms, two (2) major triacylglycerols, namely triolein (OOO) and l-palmitoyl-2- oleoyl-3-oleoyl-rac-glycerol (POO) and at least ten (10) other minor triacylglycerols were identified. The percentage (w/w) of triolein (OOO) in neutral lipid of the fat tissues from both viscera and cuticle was found to be 50% whereas that of l-palmitoyl-2-oleoyl-3-oleoyl-racglycerol (POO) was 41.7%. Other minor triacylglycerols identified in the neutral lipid of fat tissue from viscera were l-palmitoyl-2-oleoyl-3-linolenoyl-rac-glycerol, POLn (0.6%), 1- palmitoyl-2-linoleoyl-3-linoleoyl-rac-glycerol, PLL (0.1%), l-palmitoyl-2-palmitoyl-3- linoleoyl-rac-glycerol, PPL(1.1%) and l-palmitoyl-2-stearoyl-3-linoleoyl-rac-glycerol, PSO (2.9%) whereas that of cuticle were POLn (0.2%), PLL (1.0%), PPL(1.1%) and PSO (2.9%).